Correction: Ziyanok-Demirtas, S. A Holistic In Silico and In Vivo Approach to Exploring the Antidiabetic, Antioxidant, and Hepatoprotective Properties of Rose of Sharon. Life 2024, 14, 686 - Sedef Ziyanok-Demirtas (Life)
In the original publication [...]